The role of governance models in the development of transport infrastructure megaprojects in Greater Montreal: The case of the Réseau express métropolitain - Taki Imrani, Mohammed Kamal; Champagne, Eric (Frontiers in Political Science, 2023)
This article focuses on mobility issues in Montreal, whose metropolitan transportation policies are presented as one of the major ambitions of large North American metropolitan areas. Empirically, we are interested in a recent transportation megaproject: the Réseau express métropolitain (REM) in Montreal, an electric light-rail transit network spanning 67 kilometers in the Greater Metropolitan Area. These types of megaprojects involve significant governance challenges and certain criticisms due to the involvement of several actors from different backgrounds and defending different interests, which places. This is why we believe that it is important to address this issue from the point of view of metropolitan governance through the agenda-setting of urban megaprojects. The originality of this article is that it demonstrates how presenting the REM project as a public-public partnership, between the Caisse de dépôt et placement du Québec (CDPQ) and the Government of Québec, opened the door to favoritism for the Caisse which influenced the choice of a political solution in Greater Montreal. By mobilizing Kingdon's model, we conclude that windows of opportunity cannot open without choosing a governance model during the agenda-setting phase.